IMPLEMENTATION OF RISK-BASED BUSINESS LICENSING REGULATIONS FOR MSMES IN INDONESIA - Lenny Mutiara Ambarita (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This study discusses the implementation of risk-based business licensing regulations for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through the Online Single Submission Risk-Based Approach (OSS-RBA) system. This policy is part of the business licensing reform aimed at simplifying procedures, increasing business formality, and strengthening MSME competitiveness. The research method used is a descriptive qualitative approach with data collection techniques through literature studies, policy documentation, and analysis of various relevant official sources. The results show that risk-based licensing provides significant convenience for MSMEs, especially in the issuance of Business Identification Numbers (NIB) for low-risk businesses. However, the implementation of the policy still faces several obstacles, such as low digital literacy among MSMEs, limited internet access, difficulties in selecting KBLI (Indonesian Business Identification Number), minimal socialization, and technical constraints in the OSS-RBA system. The central and regional governments have an important role in supporting the success of implementation through system improvements, mentoring, socialization, and strengthening licensing services at the regional level. This study concludes that the effectiveness of the policy is quite visible in increasing the formality of MSMEs, but still requires further policy support so that the benefits of business legality have an impact on the sustainable development of MSMEs.